Croatian guidelines for specific preventive treatment of migraine with monoclonal antibodies targeting calcitonin gene-related peptide (CGRP) (eptinezumab, fremanezumab, and galcanezumab) or the CGRP receptor (erenumab) - Davor Jančuljak; Damir Petravić; Darija Mahović Lakušić; Arijana Lovrenčić-Huzjan; Koraljka Bačić Baronica; Marijana Bosnar Puretić; Zlatko Hucika; Marina Titlić; Zvonimir Popović; Zoran Tomić; Maristela Stojić; Vanja Bašić Kes (Acta Clinica Croatica)
Calcitonin gene-related peptide (CGRP) plays a key role in the pathophysiology of migraine, acting on CGRP receptors in the trigeminovascular system, causing neurogenic inflammation and vasodilation, and promoting nociception. Four specific monoclonal antibodies targeting CGRP are available for prevention of episodic and chronic migraine in adults with at least four migraine days per month. The aim of these guidelines is to provide evidence-based recommendations for the use of monoclonal antibodies targeting CGRP in migraine prevention in Croatia. The questions were formulated using the Patients, Intervention, Comparison, Outcome (PICO) criteria, with evidencebased answers. To assess the quality of scientific evidence, a review of the literature available in PubMed was performed. Relevant studies were reviewed by the Expert Group of the Headache Section of the Croatian Neurological Society, and served as the basis for formulating the recommendations outlined in these guidelines. We found high quality evidence for good safety and efficacy of anti- CGRP monoclonal antibodies in the preventive treatment of episodic and chronic migraine. These medications may be considered as first-line prophylactic therapy depending on the patient’s history, concomitant diseases, and disease burden. Further real-world studies are needed to elucidate other aspects of their application.